Analysis of mode III interlaminar fracture toughness of composite materials - Gökçen, M. Gökhan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1999., 1999)
The demand for advanced materials stimulates the research on composites, which provide high stiffness and high toughness. One failure type is delamination or interlaminar fracture, which is analyzed in three modes employing fracture mechanics. Although testing of mode I and II fractures are well established, the characterization of mode III is incomplete. The edge crack torsion (ECT) specimen seems to be the most promising configuration.In this thesis a 3-D finite element model of ECT specimen having a stacking sequence of [90/(±45)3/(45)3/90]s is developed. Using virtual crack closure technique, distribution of the individual components of strain energy release rate, G, along the crack front is obtained and the percentage of mode III component G is determined. Several finite element models are constructed to investigate the effect of specimen dimensions on the percentage of GIII intending to contribute to the optimization of ECT specimen. The results of finite element analysis revealed that %GIII extends up to 98% with increasing length and decreasing width. The corresponding length is 133.4 mm and the width is 19.1 mm. The proposed dimensions will provide necessary data to redesign the fixture for the interlaminar fracture toughness in mode III using edge crack torsion (ECT) specimen.
Keywords: Composite materials.; Composite materials -- Delamination.; Fracture mechanics.